Hypochlorous acid inhibition by acetoacetate: Implications on neutrophil functions - Da Costa, Miriani [UNESP]; Ximenes, Valdecir Farias [UNESP]; Da Fonseca, Luiz Marcos [UNESP] (Pharmaceutical Society of Japan, 2004)
Type-1 diabetic patients experience hyperketonemia caused by an increase in fatty acid metabolism. Thus, the aim of this study was to measure the effect of ketone bodies as suppressors of oxidizing species produced by stimulated neutrophils. Both acetoacetate and 3-hydroxybutyrate have suppressive effect on the respiratory burst measured by luminol-enhanced chemiluminescence. Through measurements of hypochlorous acid production, using neutrophils or the myeloperoxidase/H2O2/Cl- system, it was found that acetoacetate but not 3-hydroxybutyrate is able to inhibit the generation of this antimicrobial oxidant. The superoxide anion scavenging properties were confirmed by ferricytochrome C reduction and lucigenin-enhanced chemiluminescence assays. However, ketone bodies did not alter the rate of oxygen uptake by stimulated neutrophils, measured with an oxygen electrode. A strong inhibition of the expression of the cytokine IL-8 by cultured neutrophils was also observed; this is discussed with reference to the antioxidant-like property of acetoacetate. © 2004 Pharmaceutical Society of Japan.
Keywords: Cytokine; Hypochlorous acid; Ketone body; Myeloperoxidase; Neutrophil; Respiratory burst; 3 hydroxybutyric acid; acetoacetic acid; cytochrome c; hypochlorous acid; interleukin 18; ketone body; lucigenin; myeloperoxidase; oxygen; superoxide; acetoacetic acid derivative; interleukin 8; cell culture; cell function; cell stimulation; chemoluminescence; controlled study; human; human cell; neutrophil; oxygen electrode; respiratory burst; biosynthesis; drug antagonism; in vitro study; luminescence; metabolism; physiology; Acetoacetates; Humans; Hypochlorous Acid; Interleukin-8; Ketone Bodies; Luminescence; Neutrophils